Improving Resilience and Mental Health Occupational Therapy Involvement in School for Early Teenagers: A Scope of Review - Chanakarn Kumkun, Supat Chupradit (International Journal of Advanced Science and Technology, 2020)
The article of “Improving Resilience and Mental Health Occupational Therapy Involvement in School for Early Teenagers: A Scope of Review” that was scoped of literature review which objects to collect and review the occupational theory and concept, relevant articles and literatures about resilience. The methodology was the process of summarizing various evidences for delivering based on non-empiricaldesign. It was collected information in secondary sources of research articles, international journals, electronic sources, and theories. The result is illustrated Teenage is a period of change in physical, mental, and social, whose possible causes include internal and external factors. This period with resilience will be capable to tackle obstacles and difficulties in their life, and resilience can be improved by activities meaningful and significant for the person. The researcher suggested to develop a resilience improvement program in order to strengthen academic skills of students between 10-13 years old, by applying the process of psychosocial activities in school contexts.